Integration of Fodder Crops into cropping systems for alleviating fodder shortages - Kumari, V Visha; Srinivas, K; Balloli, S S; Maruthi, V; Ramana, D B V; Prabhakar, M; Kumar, Manoranjan; Indoria, A K; Osman, Mohammed; Chary, G R; Maheswari, M; Rao, Ch Srinivasa (Indian Farming, 2018)
Inclusion of easily propagated annual/ perennial forage legumes or grasses in the existing cropping system can address the problem of fodder shortage in rainfed areas. Theygrow fast and cover the land surface quickly even under low rainfall situations and provide considerable amount of green fodder throughout the year. Further, they help in increasing the crop yields and resource use efficiency through their vegetation cover and above - below ground interactions. Such options could be explored to identify suitable crop-fodder systems for individual locations.